If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2g + -1) = 13g Reorder the terms: 2(-1 + 2g) = 13g (-1 * 2 + 2g * 2) = 13g (-2 + 4g) = 13g Solving -2 + 4g = 13g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-13g' to each side of the equation. -2 + 4g + -13g = 13g + -13g Combine like terms: 4g + -13g = -9g -2 + -9g = 13g + -13g Combine like terms: 13g + -13g = 0 -2 + -9g = 0 Add '2' to each side of the equation. -2 + 2 + -9g = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -9g = 0 + 2 -9g = 0 + 2 Combine like terms: 0 + 2 = 2 -9g = 2 Divide each side by '-9'. g = -0.2222222222 Simplifying g = -0.2222222222
| 5/8times3/4 | | 3(2x+5)=4x-8 | | 36n=21 | | 1,200=200-m/50 | | 5/83/4 | | 104p^2-161p+28=-p^2 | | 48q+85=89 | | 5a^2+29a+10=0 | | -5(2b+5)=-105 | | 2x-7x-60=0 | | 2x=5y+9 | | -5x+[x]=25 | | 11b^2+134b+242=-4b-7b^2+2 | | 9x+5=112 | | g+30/9=7 | | 3a+2a=9c+6c | | e+192=-8e-6 | | -3(4-3k)=3(3-4k) | | x+185=-7x-7 | | r/12 | | 4(x-2)=-3+6 | | 3+4(1-3n)=-89 | | 13s+6=s-318 | | -3(4-3k)=3(-4k) | | d-173=-5d-5 | | (180-3x)+(180-2x)+324=720 | | 20=m/3+17 | | c-274=7c-4 | | n-108=5n-20 | | 1/5x-9=3/4 | | 7(8x-2)=-126 | | 6y+3y=15 |